Application to Determine Toddler Nutritional Status Using a Web-Based Fuzzy Mamdani Method - Khoirunnisya; Nurhasanah; Kevin Novebrianto (LPPM Politeknik Aceh Selatan, 2025)
The nutritional status of toddlers is vital for assessing their health and growth, but it involves many interrelated variables, making it complex to determine. The Fuzzy Mamdani method, developed by Prof. H.J. Zimmermann in the 1970s, uses fuzzy logic to handle concepts like